Combined laser and robotic approach for the management of a mixed laryngomucocele. Issue 1 (March 2016) - Lisan, Q.; Hoffmann, C.; Jouffroy, T.; Hans, S.
Abstract Treatment of laryngoceles is surgical resection, through an external approach for external laryngoceles and through an endoscopic approach for internal laryngoceles. We report the first case of a mixed laryngomucocele treated with transoral robotic surgery. A patient presented with a history of chronic cough. Nasolaryngoscopy showed a sub-mucosal swelling into the larynx. Computed tomography confirmed the diagnosis of a right mixed laryngomucocele. A transoral robotic- and laser-assisted surgery was performed. Oral feeding was started on the first post-operative day. No post-operative complication was observed. There has been no evidence of recurrence during the following months. The generally used external and endoscopic approaches each have their limits in the treatment of laryngoceles. Transoral robotic surgery allows a minimally invasive approach with a wide exposure, making possible an absence of scar and a good functional recovery after the operation. Transoral robotic approach seems to allow an endoscopic approach for mixed and external lesions. Transoral robotic surgery combined with laser is an efficient minimally invasive technique and is the best option for the treatment of mixed laryngoceles and laryngomucoceles.